Powering Up Learning: How Interactive PowerPoint Transforms Student Engagement and Outcomes in Biology - Dea Andini; Harahap, Hasmi Syahputra; Machrizal, Rusdi (Utamax : Journal of Ultimate Research and Trends in Education, 2024)
Innovative learning media, designed to meet students' needs, can boost motivation and improve learning outcomes. One such medium is interactive PowerPoint. This study aims to explore how developing interactive PowerPoint presentations affects students' motivation and their understanding of virus-related biology material. We adopted an experimental approach, comparing the effects on a control group and an experimental group chosen through random sampling. We assessed motivation through questionnaires and learning outcomes with multiple-choice tests, analyzing the data with covariance analysis (ANCOVA) at a significance level of 0.05 using SPSS 21.0. Our findings reveal that interactive PowerPoint significantly enhances both student motivation and learning achievements. Specifically, students learning with interactive PowerPoint (average score of 44.19 ± 13.175) performed significantly better than those in the control group (average score of 34.49 ± 12.433). Furthermore, motivation levels in class X3 (83.38 ± 6.605) were notably higher than in class X4 (82.58 ± 8.866). These results underline the impactful role of interactive PowerPoint in biology education, particularly for virus topics, suggesting it's a valuable addition to the curriculum. This finding offers fresh insight into the ongoing relevance and effectiveness of PowerPoint as an educational tool in biology, demonstrating its substantial benefits in presenting biological concepts in modern teaching strategies.